Digitalisasi Pembayaran Zakat Dalam Upaya Meningkatkan Efektivitas Penghimpunan Dan Pengeloaan Zakat (Studi Kasus Baznas Kota Malang) - Maimuna, Islamiyah; Eko Suprayitno; Khusnudin (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Zakat digitalization is a form of technological adaptation in the Islamic financial system aimed at optimizing the collection and management of zakat in an efficient, transparent, and well-targeted manner. Despite the vast potential of zakat in Indonesia, actual collection remains low. Moreover, challenges such as distribution inequality and limited digital literacy persist in society. In response, BAZNAS Kota Malang has begun to adopt various digital platforms in its zakat services. This study aims to identify and analyze the effectiveness of zakat collection and management at BAZNAS Kota Malang, to examine the strategies used to increase youth participation through digital platforms, and to assess the conformity of digital zakat payment contracts with sharia principles. The research employs a qualitative approach with a case study method. Data were obtained through interviews, observation, and documentation. The findings indicate that zakat digitalization has improved the effectiveness of zakat collection and management by enhancing accessibility, transaction efficiency, and transparency. BAZNAS Kota Malang utilizes various digital channels such as an official website, e-wallets, QRIS, and collaborations with Islamic banks. However, challenges remain, particularly regarding the sharia compliance of digital contracts and uneven levels of digital literacy in the community. This study recommends ongoing education and the strengthening of sharia aspects in digital zakat services.